The Legal Status of Surrogate Mothers in Indonesia - Dinarjati Eka Puspitasari (Batulis Civil Law Review, 2022)
The practice of surrogate mother is widely applied abroad, but in Indonesia there is a lot of opposition from the community. In Indonesia, this practice has not received a clear legal force. This is related to the clarity of the legal status of the child being born as well as the legal status of the rent of the womb of another person who has not been regulated. The purpose of this study is to determine the legal position of surrogate mother and its implementation based on ethics and religion in Indonesia. This study uses a normative juridical approach. The results of this study indicate that surogate mother in Indonesia is null and void because it is contrary to Article 1320 of the criminal code; in addition, from the side of criminal law is also contrary to Article 284 of the Criminal Code. Even surrogate mother declared not in accordance with the norms of decency in Indonesia.